SISTEM PENGENDALIAN INTERNAL UNTUK MEMINIMALKAN KREDIT BERMASALAH STUDI PT. PEGADAIAN (PERSERO) UPC PARE - Amanah, Anandatul; Astuti, Puji; Nurdiwati, Diah (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
This study aims to determine the internal control system applied in minimizing non-performing loans and how to resolve the occurrence of non-performing loans. This research is a descriptive research as well as a qualitative approach. In data collection procedures used are observation, interviews, documentation and library research. The data sources used primary data, secondary data and qualitative, descriptive data analysis techniques. The results of this study indicate that the internal control system in minimizing non-performing loans is good and in accordance with COSO theory although there are weaknesses in the control environment and controlling activities where there are still multiple positions. Settlement of non-performing loans by rescheduling, reconditioning, restructuring and execution. The researcher suggests that additional employees and segregation of duties be carried out between the estimator and the depositor of collateral